SEJARAH DAN PERKEMBANGAN SENI KALIGRAFI DALAM ISLAM - Ashrafah Aulia; Firmansyah Firmansyah (Jurnal Shaf, 2024)
Calligraphy is one of the art of painting with Arabic inscriptions in Islamic art. Calligraphy can also be said as knowledge and skills for every artist. From each carving, calligraphy has its own meaning in it. The application of the method in this study is a qualitative method and literature analysis. The data collection process in this study determines the art of literature related to the studies discussed, the data analysis in this study uses normative analysis. The results of this study state that the history of calligraphy has a special meaning both in writing and in meaning. The art of calligraphy also experienced further development of Umayyad, Abbasid, & Abbasid writings. The development of writing that is still used today, namely during the late Abbasid period, especially in Islamic countries.